Fungal pneumonia in kidney transplant recipients. (August 2021) - Wilmes, D.; Coche, E.; Rodriguez-Villalobos, H.; Kanaan, N.
Abstract: Fungal pneumonia is a dreaded complication encountered after kidney transplantation, complicated by increased mortality and often associated with graft failure. Diagnosis can be challenging because the clinical presentation is non-specific and diagnostic tools have limited sensitivity and specificity in kidney transplant recipients and must be interpreted in the context of the clinical setting. Management is difficult due to the increased risk of dissemination and severity, multiple comorbidities, drug interactions and reduced immunosuppression which should be applied as an important adjunct to therapy. This review will focus on the main causes of fungal pneumonia in kidney transplant recipients including Pneumocystis, Aspergillus, Cryptococcus, mucormycetes and Histoplasma. Epidemiology, clinical presentation, laboratory and radiographic features, specific characteristics will be discussed with an update on diagnostic procedures and treatment. Highlights: Fungal pneumonias are dreaded infections in KTR associated with increased mortality. Dissemination is frequent and can involve the central nervous system. Treatment should be initiated as soon as the diagnosis is considered. Antifungal drugs carry risks of drug interactions with immunosuppressants. Reducing immunosuppression is an important adjunct to treatment.